Revenue decline in urban local authorities: A case study of Gweru City Council. - Moyo, Tanya N. T. (Midlands State University, 2017)
The research analysed the sources of revenue and the causes and effects of revenue decline in urban local authorities. The research was prompted by the evident decline in revenue inflows in most of the urban local authorities in Zimbabwe as the traditional sources of revenue have gone dry and this has heavily impacted on their performance. To achieve the objectives of the study, literature sources were reviewed and both secondary and primary sources were employed to obtain data on the subject under study. The study highlighted and analysed the various views of other authors on the sources of revenue for local authorities, and the causes and effects of revenue decline in local authorities. The study also presented empirical evidence and global experiences in terms of revenue collection. The research targeted the population consisting of members of the Caretaker council, Management, Workers committee and Gweru residents and ratepayers association. A sample size of 39 participants was chosen for the study through judgmental and simple random sampling. The findings of the research were presented in the form of tables, pie charts and graphs. Data analysis revealed that Gweru city council was performing poorly in terms of service delivery due to a decline in revenue inflows and identified the causes of revenue decline as attributed to poor billing system, political influence, economic challenges, corruption and resistance of ratepayers in paying bills. The effects of revenue decline were established as the decline in service delivery, garnishing of council accounts, downsizing and late payment of salaries and allowances to its employees thus affecting the performance of the organization as a whole. The study concluded that Gweru city council has a long way to go in getting back its title as the ‘city of progress,’ by ensuring that there is effective and efficient service delivery and this can only be achieved if there is a sound revenue base to support all its activities. The study recommended that strategies should be put in place to avert corruption, to encourage ratepayers to pay bills and to source other avenues which can boost the revenue base of the local authority.